2020
DOI: 10.1101/2020.04.21.771832
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Changing color and intensity of LED lighting across the day impacts on human circadian physiology, sleep, visual comfort and cognitive performance

Abstract: We examined whether dynamic light across a scheduled 16-h waking day influences cognitive performance, visual comfort, melatonin secretion, sleepiness and sleep under strictly controlled laboratory conditions of 49-h duration.Participants spent the first 5-h in the evening under standard lighting, followed by an 8-h nocturnal sleep episode at habitual bedtimes. Thereafter volunteers either woke up with static daylight LED (100 lux and 4000 Kelvin) or with a dynamic daylight LED that changed color (2700 -5000 K… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 75 publications
0
1
0
Order By: Relevance
“…Research suggests that there is a linkage between CCT, alertness and cognitive performance. From a study with 16 subjects, exposed to different artificial light settings for two consecutive hours during evening sessions, Chellappa et al (2011) and Stefani et al (2020) concluded that commercially available compact fluorescent lights with different color temperatures could significantly affect circadian physiology and cognitive performance. As for DWl, studies have shown that suppression of melatonin is more sensitive to light at shorter wavelengths, with the predominance of the blue spectrum as the most effective for the maintenance of circadian functions (Brainard et al, 2001;Thapan et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Research suggests that there is a linkage between CCT, alertness and cognitive performance. From a study with 16 subjects, exposed to different artificial light settings for two consecutive hours during evening sessions, Chellappa et al (2011) and Stefani et al (2020) concluded that commercially available compact fluorescent lights with different color temperatures could significantly affect circadian physiology and cognitive performance. As for DWl, studies have shown that suppression of melatonin is more sensitive to light at shorter wavelengths, with the predominance of the blue spectrum as the most effective for the maintenance of circadian functions (Brainard et al, 2001;Thapan et al, 2001).…”
Section: Introductionmentioning
confidence: 99%